WAY OF THE SAMURAI: UNDERSTANDING JAPAN’S ENERGY SECURITY STRATEGY POST-FUKUSHIMA DISASTER - Ibrahim Hugo; Indra Kusumawardhana (Universitas Nasional, 2023)
The Fukushima Disaster in 2011 posed a challenge to Japan's energy security. Before the disaster, Japan was very dependent on nuclear power plants to fulfill its energy mix, mainly the Fukushima Daiichi Nuclear Power Plant. Energy security is prominently Japan's priority agenda because they do not possess natural resource endowments. Therefore, Japan must pay attention to provide energy availability access, emphasizing accessibility elements to maintain a secure position at global economic levels. Departing from this background, this paper analyzes Japan's energy security strategy after the Fukushima Disaster. The article questions the post-Fukushima Disaster, How does Japan maintained their energy security under the dynamics of current geopolitics of energy after Fukushima Disaster?. The finding obtained from the analysis is that Japan focuses on import policy to fulfill its national energy security. Meanwhile, the current international political situation has prosecuted Japan to China's foreign policy competitiveness and its impact on the geopolitical map. Moreover, Japan's energy security strategy is based on energy policy amid geopolitical energy competition to pursue energy security through two levels, namely the domestic and international sectors.